PENGARUH MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BERBASIS SOCIO-SCIENTIFIC ISSUES (SSI) TERHADAP PENINGKATAN KETERAMPILAN LITERASI SAINS SISWA - Ramadhanti, Novita Hari; Astriani, Dyah (PENSA E-JURNAL: PENDIDIKAN SAINS, 2024)
This research aims to determine the effect of the SSI-based type-STAD cooperative learning model on scientific literacy skills at SMP Muhammadiyah 2 Taman Sidoarjo. This research uses quantitative research using the Pre Experimental Design method, with a research design plan of one group pretest-posttest design. Data were analyzed using SPSS with paired t-test results with Sig values. (2-tailed) is less than 0.01 < 0.05, so it can be concluded that H0 is rejected and Ha is accepted, meaning that there is an influence of the SSI-based type-STAD cooperative learning model on Scientific Literacy abilities. The magnitude of significance is measured by Effect Size, the results of the Effect Size on students’ scientific literacy abilities are 2.225 in the very large category. This shows that the SSI-based type-STAD cooperative learning model has an influence on students’ scientific literacy abilities.